PENATALAKSANAAN HOLISTIK PASIEN LAKI-LAKI USIA 27 TAHUN DENGAN VARISELA MELALUI PENDEKATAN DOKTER KELUARGA DI WILAYAH KERJA PUSKESMAS SUKARAJA - Suwanda, Meyliana; Nusadewiarti, Azelia (CV. Jasa Sukses Abadi, 2024)
Varicella or chicken pox is an acute and highly contagious disease caused by infection with the Varicella Zoster virus (VZV). Apply the principles of family medicine services and carry out holistic management based on a framework for solving patient problems with a patient-centered, family focused and community-oriented approach based on Evidence Based Medicine. This study analysis is a case report. Primary data is obtained through history taking, physical examination and home visits to complete family data, psychosocial and environmental data. Secondary data was obtained from patient medical records at the Community Health Center. The assessment is carried out based on a holistic diagnosis of the beginning, process and end of the study quantitatively and qualitatively. Male patient Mr. C 27 years-old came with complaints that he had tingles on his face, neck, body, back, arms, and leg for two days ago accompanied by itching. Elastic in the form of vesicles the size of billions, round shape, well-defined, with an erythematosus base, distributed regionally. Clinically and on physical examination the patient was diagnosed with Varicella (ICD 10 B01.9). In this case, diagnosis and treatment have been carried out according to theory and related journals. After the intervention was carried out, there was a reduction in clinical symptoms and an increase in patient and family knowledge. Holistic management can improve the knowledge, attitudes and behavior of patients and families in maintaining health.